Internet integrated service over ATM a solution for shortcut QoSvirtual channels. - Cocca, R. (IEEE Communications magazine)
In principle, the interaction of the resource reservation protocol (RSVP) and ATM should allow the IP level to benefit from some features of the ATM layer. The most interesting one is the native support of end-to-end quality of service provided by ATM. On the other hand, there are issues that must be clarified to define correct interworking: for example, the possible overlapping between the mechanisms used in the IP and ATM levels to support QoS, or the needed IP/ATM address resolution mechanism. This article proposes a solution to exploit ATM shortcut VCs supporting QoS in the Internet integrated services model. A straightforward enrichment to the RSVP protocol is defined, which only impacts the devices (hosts and routers) involved in the shortcut procedure. A mechanism for IP/ATM address resolution is provided, avoiding the use of other mechanisms such as NHRP. Special care has been taken to maintain compatibility with ?traditional? RSVP hosts and routers